2017
DOI: 10.2528/pierc17082308
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Element Antenna Array at 3.5 GHZ for Mimo Wireless Application

Abstract: Abstract-A multiple-input-multiple-output (MIMO) antenna array with eight printed coplanar waveguide (CPW)-fed monopole antennas operating at 3.5 GHz (3.4-3.6 GHz) is presented. Each antenna is an Inverted-L (IL) monopole surrounded by a parasitic IL-shorted stripe and attains compact configuration. Both the IL-monopole and parasitic IL-shorted stripe contribute their fundamental resonant modes to operate in the desired frequency band. The neutralization line (NL) and ground middle slot are used for decoupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…In addition, its TARC value is less than −30 at 3.6 GHz. Table 2 summarizes and compares the fundamental characteristics of the presented mobile-phone antenna with the recently reported 5G mobile-phone antenna designs [16][17][18][19][20][21][22][23][24][25]. It can be observed that the proposed design can provide better performances in terms of efficiency, isolation and ECC.…”
Section: Mobile-phone Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its TARC value is less than −30 at 3.6 GHz. Table 2 summarizes and compares the fundamental characteristics of the presented mobile-phone antenna with the recently reported 5G mobile-phone antenna designs [16][17][18][19][20][21][22][23][24][25]. It can be observed that the proposed design can provide better performances in terms of efficiency, isolation and ECC.…”
Section: Mobile-phone Antenna Designmentioning
confidence: 99%
“…According to the requirement of cellular communications, compact, wideband and high isolation MIMO antenna is an urgent demand in the future mobile terminal and the portable applications [12][13][14][15][16][17]. Recently, several techniques have been introduced to design massive MIMO antennas for 4G and sub-6 GHz 5G mobile terminals [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As seen, the design has less than − 20 dB TARC values at different frequencies. The fundamental properties of the proposed MIMO diversity antenna system are compared with the recently reported MIMO antenna designs and are listed in Table 3 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. As clearly seen, in contrast to the recently proposed designs, the designed MIMO antenna offers ultra- Another important function is the channel capacity loss (CCL) of the MIMO system [43], which mainly depends on the S-parameters of the MIMO system with the accepted limit of ≤0.4 bps/Hz and can be calculated while using the below formulas:…”
Section: The Proposed Uwb Diversity Antenna Systemmentioning
confidence: 99%
“…Several MIMO 5G smartphone antennas have been recently proposed [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, these smartphone antennas either suffer from narrow impedance-bandwidth (either single-band or dual/multi-band) or use single-polarized uniplanar antenna resonators occupying large spaces of the mainboard, which leads to increasing the complexity of the mobile phone system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation